Multimedia signal processing : theory and applications in speech, music and communications - Vaseghi, Saeed V. (J. Wiley, 2007)
The aim of this book is to provide a coherent and structured presentation of the theory and applications of statistical signal processing in three sections: Part 1: Basic Digital Signal Processing, which gives an introduction to the topic, discussing sampling and quantization, Fourier analysis and synthesis, Z-transform, and digital filters; Part 2: Model-based Signal Processing that covers probability and information models, Bayesian inference, Wiener filter, adaptive filters, linear prediction and hidden Markov models; and, Part 3: Applications of Signal Processing in Speech, Music, and Telecommunication, which explains the topics of speech and music processing, echo cancellation, deconvolution and channel equalization, and mobile communication signal processing.